Platelet count and its indices-effectiveness in early diagnosis of neonatal sepsis - Singh, Priti; Chandar, Vipin (Indian Journal of Child Health, 2025)
Context: Neonatal sepsis is the major cause of morbidity and mortality in developing countries requiring early diagnosis and treatment. The Gold standard Blood culture results are often delayed for 48 h with high false-negative values. Emerging evidence suggests that platelet indices such as plateletcrit, mean platelet volume (MPV), and platelet distribution width (PDW) are reliable biomarkers that are readily available while obtaining routine complete blood counts. Aim: The aim of the study was to evaluate the efficacy of platelet count (Platelets) and its indices in the early diagnosis of sepsis. Settings and Design: Blood samples were collected from all neonates admitted to the hospital with features of suspected sepsis. Materials and Methods: One hundred patients were recruited for this cross-sectional analytical prospective study. All neonates delivered in Himalayan Institute of Medical Sciences and those referred from outside with features of suspected septicemia meeting the inclusion criteria were taken for study purposes. Blood samples were collected at the time of admission. Patients were divided into three groups clinically suspected sepsis (probable sepsis), culture-positive sepsis, and culture-negative sepsis. Non-parametric tests like the Chi-square test were applied to see the association between the variables. The three groups were compared for Platelets and its indices with the Analysis of variance test. Results: MPV was 219.2, 174.8, and 205.7 (p